Determining Behavior to Uptake and Its Predictors toward Cervical Cancer Screening among Women: A Case-Control Multistage Study - Eko Winarti; Dhita Kris Prasetyanti; Moh Alimansur; Rozzana Mohd Said (Jurnal Keperawatan Padjadjaran, 2021)
Background: Cervical cancer is a primary cause of mortality cancer among Indonesian women. Notwithstanding these threats, cervical cancer screening services have low uptake. Additionally, there was a lack of multistage case-control studies regarding positive behavior and its determinants for cervical cancer screening. Purpose: This study was to ascertain the uptake behavior and its predictors toward cervical cancer screening. Methods: A case-control study was conducted in Kediri with a sample size of 410 using multistage random sampling (ratio 1:1) from nine community health services and data were collected between June 11 to September 18, 2019. Data were obtained through questionnaires and assessed using Chi-square, Independent t-test, and multiple logistic regression with adjusted odds ratio (AOR). Results: Behavior of cervical cancer screening was related to knowledge (AOR= 1.61), husband support (AOR= 1.38), social support (AOR= 5.03), external motivation (AOR= 1.24), internal motivation (AOR= 1.37), perceived susceptibility (AOR= 1.49), perceived barrier (AOR= 0.74), perceived benefit (AOR= 0.73), perceived severity (AOR= 1.36), self-efficacy (AOR= 1.30), perceived threat (AOR= 1.26), and intention to screening (AOR= 3.06) with p value <0.05 after adjusting covariate factors. Conclusion: Knowledge, husband and social support, external and internal motivation, all domains of health belief, and intention to uptake screening were found to be strongly associated with behavior to uptake cervical cancer screening.